Performance Of Optical Label Switching Network With Multi Protocol Label Switching Implementation - Kaspin, Rizaludin (2002)
Today, the phenomenal traffic growth of Internet leads to the dramatic expansion of the transmission lines in the Internet Protocol (IP) network. Fibre optics as the key of the future transmission networks has evolved to provide almost limitless information carrying capacity via its Wavelength Division Multiplexing (WDM) technology. However, the relatively sluggish development in switching technology which still operates in electronics domain might creates bottleneck in various part of the network. Thus, the concept of All-Optical Network has been introduced. Here a lot of approaches have been proposed to bring IP closer to the optics technology such as IP over WDM. On the other hand, IP technology itself has evolved from pure connectionless system to connection-oriented in order to cope with the Quality of Service (QoS) demanded by the end users. Thus, the concept of Multi Protocol Label Switching (MPLS) has been standardized to achieve this. In this thesis, connection-oriented Optical Label Switching (OLS) network implementing MPLS system has been proposed as a viable and future proof network architecture.